27-GAUGE MICRO INCISION BIOPSY TECHNIQUE FOR TUMORS OF THE IRIS AND CILIARY BODY - K. Scripsema Nicole; T. Finger Paul (Российский офтальмологический журнал)
Purpose.To evaluate a 27-gauge aspiration-cutter technique for biopsy of anterior segment neoplasia. Methods. In this retrospective case review, all patients had clinically diagnosed iris or ciliary body tumors. Each underwent surgical iridectomy biopsy utilizing a modification of the Finger Iridectomy Technique (FIT). Specifically, a beveled clear corneal incision was created with a 27-G inked trocar. Sodium hyaluronate 1 % was infused to posteriorly displace the iris and stabilize the chamber. Then a 27-G aspiration-cutter probe was introduced into the anterior chamber, to a position over the tumor. With the aspiration portal abutting the lesion, surgical iridectomy biopsies were obtained using a cut rate of 300 cuts/min and aspiration of 600 mmHg. After each pass, the probe was removed, its tip placed in balanced salt solution and its contents aspirated into a 3-mL syringe. Each syringe was labeled by pass number and tumor location (by clock hour). After obtaining multiple biopsies, the sodium hyaluronate 1 % was removed and the integrity of the wound checked. Main Outcome Measures. Cytologic, tissue histopathology, and immunohistochemical analyses were performed for diagnostic purposes. Visual acuity, intraocular pressure control and procedure-related complications were secondary outcomes measures. Results. Diagnostic specimens were obtained in all 8 cases (100 %). Diagnoses included unifocal melanoma (62 %), diffuse multifocal melanoma (13 %), and melanocytoma (25 %). All 27-gauge corneal wounds were self-sealing. There was no secondary glaucoma, infection, cataract, or vision loss. Two patients had small transient hyphemas which resolved within 10 days. Conclusions. This study reveals that 27-gauge aspiration-cutter assisted surgical iridectomy biopsy was both minimally invasive and effective. It allowed for partial and full thickness iris biopsy. Compared to larger-gauge aspiration cutter assisted biopsy techniques, this 27-G aspiration-cutter probe allowed for even smaller corneal incisions, rapid recovery and tissue for pathology evaluation. For citation: Scripsema N., Finger P.T. A 27-gauge micro incision biopsy technique for tumors of the iris and ciliary body. Russian ophthalmological journal. 2018; 11 (3): 43-8. doi: 10.21516/2072-0076-2018-11-3-43-48